2022
DOI: 10.1371/journal.pone.0271626
|View full text |Cite
|
Sign up to set email alerts
|

Climate change and spatio-temporal trend analysis of climate extremes in the homogeneous climatic zones of Pakistan during 1962-2019

Abstract: Climate extremes, such as heat waves, droughts, extreme rainfall can lead to harvest failures, flooding and consequently threaten the food security worldwide. Improving our understanding about climate extremes can mitigate the worst impacts of climate change and extremes. The objective here is to investigate the changes in climate and climate extremes by considering two time slices (i.e., 1962–1990 and 1991–2019) in all climate zones of Pakistan by utilizing observed data from 54 meteorological stations. Diffe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 77 publications
1
11
0
Order By: Relevance
“…These indicators are helpful tools for decision-makers to manage water resources in the SRB. During the analysis, it was observed that there is a shifting pattern of temperature on a monthly basis in the SRB, and our results are in line with previous studies indicating a shifting of temperature in regions of Pakistan (Khan et al, 2022;Nawaz et al, 2019;Abbas et al, 2018;Afzaal et al, 2009;Yaseen et al, 2014). For example, del Rı ´o et al ( 2013) revealed the shifting temperature trend using Sen's slope and Mann-Kendall tests in Pakistan at monthly, seasonal and annual time scales over the past few decades and the mean annual temperature increased around 0.36 °C/decade.…”
Section: Discussionsupporting
confidence: 93%
“…These indicators are helpful tools for decision-makers to manage water resources in the SRB. During the analysis, it was observed that there is a shifting pattern of temperature on a monthly basis in the SRB, and our results are in line with previous studies indicating a shifting of temperature in regions of Pakistan (Khan et al, 2022;Nawaz et al, 2019;Abbas et al, 2018;Afzaal et al, 2009;Yaseen et al, 2014). For example, del Rı ´o et al ( 2013) revealed the shifting temperature trend using Sen's slope and Mann-Kendall tests in Pakistan at monthly, seasonal and annual time scales over the past few decades and the mean annual temperature increased around 0.36 °C/decade.…”
Section: Discussionsupporting
confidence: 93%
“…The social infrastructure is becoming increasingly susceptible to climatic extremes (i.e. heat waves, floods, and droughts), have varied effects on the economy, society, ecology, and the environment as a result of regional and global climate change (Khan et al 2022). As temperatures rise, more people contract infectious diseases like dengue and malaria in Pakistan.…”
Section: Discussionmentioning
confidence: 99%
“…It has an area of 881 912 km 2 and an elevation range of 0-8611 m that decreases southward (figure 1) (Akhtar et al 2022). The country has a complex climatology and multifaceted topography, such as the Arabian Sea to the south and the Himalayas, Hindu Kush, and Karakoram mountains to the north (Khan et al 2022). The country has four seasons (winter: December-February, spring: March-May, summer: June-August, autumn: September-November), having spatial and temporal climatic variation (Ali et al 2019).…”
Section: Study Areamentioning
confidence: 99%
“…Several techniques have been employed in identifying trends in hydrometeorological variables in recent times, including Mann-Kendall (MK) (Mann, 1945;Kendall, 1975), Sen's slope (Sen, 1968), and the linear regression trend test (Haan, 1977). The classical approach is still extensively applied worldwide for the holistic identification of meteorological variables' trends (Felix et al, 2021;Ali et al, 2019;Khan et al, 2022;Aditya et al, 2021;Gadedjisso-Tossou et al, 2021). Nonetheless, the conventional trend identification approach lacks comprehensive information in the discussion of partial trends across various levels of time series (Sen, 2012;Sen, 2014;Guclu et al, 2020).…”
Section: Trend Analysismentioning
confidence: 99%